Effects of Bacillus subtilis and Bacillus licheniformis on growth performance, immunity, short chain fatty acid production, antioxidant capacity, and cecal microflora in broilers - Xu, Yinglei; Yu, Yang; Shen, Yuanyuan; Li, Qing; Lan, Junhong; Wu, Yanping; Zhang, Ruiqiang; Cao, Guantian; Yang, Caimei (Poultry science, 2021)
This study investigated the effects of dietary supplementation with Bacillus subtilis (B. subtilis) or Bacillus licheniformis (B. licheniformis) on growth performance, immunity, antioxidant capacity, short chain fatty acid (SCFA) production, and the cecal microflora in broiler chickens. In total, 360 male, 1-day-old Cobb 500 birds were randomly divided into 3 groups: the control group was fed a basal diet; the B. subtilis group was fed a basal diet supplemented with 1.5 × 109 CFU/kg B. subtilis; the B. licheniformis group was fed a basal diet supplemented with 1.5 × 109 CFU/kg B. licheniformis. Results showed that chickens supplemented with either B. subtilis or B. licheniformis had comparatively higher (P < 0.05) body weight and average daily gain, whereas no difference (P > 0.05) was observed in feed efficiency. Concentrations of serum IgA, IgY, and IgM, as well as anti-inflammatory IL-10 were significantly increased (P < 0.05), and proinflammatory IL-1β and IL-6 were significantly decreased (P < 0.05) by B. subtilis or B. licheniformis supplementation. Moreover, chickens fed with diets supplemented by either B. subtilis or B. licheniformis had greater antioxidant capacity, indicated by the notable increases (P < 0.05) in glutathione peroxidase, superoxide dismutase, and catalase, along with decrease (P < 0.05) in malondialdehyde. Compared to the control group, levels of SCFA, excluding acetic and propionic acid, in cecal content had improved (P < 0.05) by adding B. licheniformis, and significant increase (P < 0.05) in acetic and butyric acid was observed with B. subtilis supplementation. Microbial analysis showed that both B. subtilis or B. licheniformis supplementation could increase butyrate-producing bacteria such as Alistipes and Butyricicoccus, and decrease pathogenic bacteria such as the Synergistetes and Gammaproteobacteria. In summary, dietary supplemented with B. subtilis or B. licheniformis improved growth performance, immune status, and antioxidant capacity, increased SCFA production, and modulated cecal microbiota in chickens. Moreover, B. licheniformis was more effective than B. subtilis with the same supplemental amount.